Media Massa dan Politik Islam Pasca Reformasi 1998 (Studi Historis Komparatif dan Ekonomi Politik di Sumatera Utara) - Nirwansyah Putra (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
The 1998 Reformation Movement and the No. 40/1999 Law on The Press has been widely studied. But not with the relation of mass media and Islamic politics. Questioning how the definition and meaning of Islamic politics in the media, the effects of media policy and the dynamics of Islamic politics, are serious questions that need to be developed and studied in general and specifically. Including, studying the trichotomic relationship between the State-Islam-Media. Related to, North Sumatra is already known as an area with high media intensity. This study uses a descriptive qualitative model which using historical-comparative and political-economic approach in analysis and qualitative interpretation. This paper describes the complex relations between the mass media and the dynamics of Islamic politics in the pre and post 1998 Reformation period.